Pattern of diastolic dysfunction in alcoholic and non-alcoholic cirrhotic portal hypertensive patients with or without ascites in rural population in South India - Sidmal, Prashant S.; BG, Prashanthkumar; KC, Shekarappa (International Journal of Research in Medical Sciences, 2017)
Background: Abnormalities in cardiac function have been reported in liver cirrhosis, suggesting a latent cardiomyopathy in these patients. In this study, we evaluated the association between severity of diastolic dysfunction and severity of cirrhosis in alcoholic and non-alcoholic cirrhotic patients with or without ascites in rural population in South India. Methods: This cross-sectional study was conducted on alcoholic and non-alcoholic cirrhotic patients coming from rural background admitted in a tertiary hospital in South India from January 2014 to March 2015. 60 patients were enrolled. Severity of cirrhosis was evaluated by Child-Pugh score. A 12-lead surface ECG and echocardiographic studies were performed. Results: Seventy eight percent of patients were male. The mean age of patients was 58.98 ± 15.2 years. 21%, 37%, and 42% of patients were considered as child class A, B, and C, respectively. There was a significant relation between diastolic dysfunction and disease duration (P=0.001), age >60 years (P=0.004), and severity of cirrhosis (P=0.003). Conclusions: Because of high prevalence of diastolic dysfunction in cirrhotic patients and risk of decompensation following invasive procedures, it could be suggested that all patients would be screened routinely by echocardiography before invasive procedures. According to the relation between Child-Pugh score and diastolic dysfunction, it is recommended for cardiac assessment, especially echocardiographic evaluation in all cirrhotic patients. In conclusion, left ventricular diastolic dysfunction is commonly associated with advancement of hepatic dysfunction while systolic function is maintained till advanced hepatic failure.